(untitled) (CIPEEX, 2025)
Introduction: Role-play, as an active learning methodology, has gained prominence in medical education due to its potential to integrate communication skills into professional practice. It provides experiential learning that enables students to develop empathy and teamwork, enhancing entrustability as professionals. Objective: To analyze role-play as a pedagogical strategy for teaching communication skills in medicine, correlating it with Entrustable Professional Activities (EPAs) and practice (clinic) management. Methods: A narrative review was conducted in PubMed and SciELO, focusing on studies published between 2020 and 2025 that investigated the use of role-play in medical education. Results: Evidence indicates that role-play improves empathy, confidence, and collaboration, outperforming traditional lectures in communication outcomes¹. Scenario-based role-play significantly enhances students’ performance in clinical interviews, case presentations, and breaking bad news, aligning directly with EPA requirements that include effective communication as an essential competence expected of learners². Peer role-play has been identified as a cost-effective and less stressful alternative to standardized patients, fostering reflection and self-assessment³. Moreover, role-play strengthens practice management by promoting clarity of communication, reducing errors, improving treatment adherence, and advancing patient safety⁴.The strategy also enables independent assessment of skills, ensuringthey meet required communication standards⁵.Conclusion: Implementation of this strategy is consistent with National Curriculum Guidelines across health programs. Role-play is a valuable pedagogical approach that integrates educational theory and practice, ensuring the development of entrustable communication competencies in line with EPAs and practice management. Its integration into medical curricula contributes both to professional training and to improving the quality of care and the efficiency of the health system.